Mechanical Colonic Obstruction as A Complication of Necrotizing Pancreatitis: A Case Report and Literature Review - Al-Ghamdi, Dr. Shahad; Al-Mutairi, Dr. Ayed (International Journal of Innovative Research in Medical Science, 2022)
Colon involvement in patients with severe acute or chronic pancreatitis have been seen, and complications such as paralytic ileus, segmental necrosis, and pancreaticocolonic fistulas were reported. However, mechanical obstruction of the colon due to pancreatitis is very rare. We report a case of a transverse colon mechanical obstruction in 43-year-old male, due to non-biliary necrotizing pancreatitis. Trial of conservative management were failed and emergency laparotomy with deflation of the colon, segmental bowel resection for the ischemic cecum and end ileostomy were done. In such patients radiological imaging is highly important for further examination of the colon. Management consistent of bowel resection may be required electively or acutely.